PERANCANGAN MODEL DATA WAREHOUSE PENJUALAN MATERIAL MENGGUNAKAN SKEMA BINTANG - Muhaimin Hasanudin; Haris; Muhamad Zahruddin; Boy Yuliadi (FT-TEKNIK USNI, 2019)
The development of information technology is increasing rapidly over time, making data continue to grow and develop. Data has value, meaning and benefits, if it is processed into information or for analysis needs. Along with business growth, the utilization of existing information technology is considered still lacking, because the technology only supports operational database activities. Data warehouse is present to answer the growth of businesses that require very large data, through a data warehouse the company can findout the specific needs of its customers, and the results of sales. The aim of this research is to formulate a data warehouse model that is in accordance with the results of the company's needs analysis. The methodology used in this study uses the method of analysis and design. Where in the analysis method literature studies, surveys and interviews are conducted, identifying information needed by managerial in decision making. While the data warehouse design method uses a star scheme because it is easily understood and used in the process of forming queries. The results of this study are in the form of a data warehouse model that is formed from operational data, processed in various dimensions that exist, sothat it can form a report to meet the managerial needs of information. With the existence of this data warehouse, managerial parties can analyze the reports generated from various perspectives easily